Cyber forensics : from data to digital evidence - Marcella, Albert J. (Wiley, 2012)
"An explanation of the basic principles of data. This book explains the basic principles of data as building blocks of electronic evidential matter, which are used in a cyber forensics investigations. The entire text is written with no reference to a particular operation system or environment, thus it is applicable to all work environments, cyber investigation scenarios, and technologies. The text is written in a step-by-step manner, beginning with the elementary building blocks of data progressing upwards to the representation and storage of information. It includes practical examples and illustrations throughout to guide the reader"--